2020
DOI: 10.1186/s12909-020-02320-0
|View full text |Cite
|
Sign up to set email alerts
|

Levelling the playing field: students’ motivations to contribute to an amnesty of assessment materials

Abstract: Background ‘Exam recall’ is a recognised phenomenon whereby students recall and record questions after leaving the examination hall. This poses two main problems. First, as these questions are only available to peers of the students who recall the questions, these individuals have an unfair advantage. Secondly, the distribution of these recalled questions poses a threat to the validity and defensibility of assessments. To address the first of these problems, we developed an amnesty enabling students to submit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Participants across both focus groups highlighted how the CM had provided transparency on ILOs. This was recognised as crucial for tackling the perceived inequalities stemming from information-sharing across student societies [ 5 ]: “Because I feel like…most of us do have friends in the years above and we can ask for advice…but I feel it…just levels the playing field and everyone has got a curriculum that they can refer to and no one feels, like, disadvantaged .” (FG 4-5, Female-4) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants across both focus groups highlighted how the CM had provided transparency on ILOs. This was recognised as crucial for tackling the perceived inequalities stemming from information-sharing across student societies [ 5 ]: “Because I feel like…most of us do have friends in the years above and we can ask for advice…but I feel it…just levels the playing field and everyone has got a curriculum that they can refer to and no one feels, like, disadvantaged .” (FG 4-5, Female-4) …”
Section: Resultsmentioning
confidence: 99%
“…Feedback from the National Student Survey, Staff Student Consultative Committees and Staff Evaluation Questionnaires, revealed that some students felt at a disadvantage due to the lack of clarity around curriculum and assessments [ 5 , 6 ]. To address this, a Curriculum Mapping Team (CMT) was established in 2018, consisting of an Academic Lead, Clinical Teaching Fellow (CTF), Project Manager and Learning Technologist.…”
Section: Introductionmentioning
confidence: 99%
“…Another key issue reinforced by this study was students' perception that learning is principally for passing exams ('assessment drives learning'), as has been borne out in many studies throughout education and medical education in the past [29]. Assessment forms a critical component for many courses of study but specifically in the MBBS programme, it ensures an appropriate level of competency and safety for students entering the profession [5].…”
Section: Discussionmentioning
confidence: 99%
“…Some students reported feeling disadvantaged in accessing key Fig. 1 UCLMS Core Curriculum materials if they were not members of student societies or sports club where it was reported that sharing of assessment material occurred [29]. In order to improve clarity around the syllabus, outline content for assessment, and improve the student experience, the faculty took a strategic decision to create and embed a single source of curricular knowledge: the MBBS Curriculum Map.…”
Section: Why Develop a Curriculum Map At Uclms?mentioning
confidence: 99%